Isolated HBsAg positivity in a Mexican patient with newly diagnosed lupus nephritis - Delgado García, Guillermo Rubén; Mandujano Cruz, Ilse; González Padilla, Kiber; Alarcón Galván, Gabriela; Villarreal Alarcón, Miguel Ángel; Galarza Delgado, Dionicio Ángel (2016)
Abstract Introduction: Hepatitis B surface antigen (HBsAg) is usually regarded as a marker of hepatitis B virus (HBV) infection. The concurrence of lupus nephritis (LN) and HBsAg-positivity is a challenge for the clinician, since immunosuppressant use may be associated with an increase in viral replication and an exacerbation of liver disease. Case presentation: Here, we describe the case of a 30-year-old Mexican woman with newly diagnosed focal proliferative LN who also tested repeatedly positive for HBsAg by chemiluminescent microparticle immunoassay (CMIA). She had no clinical features of hepatitis and her liver function tests were within normal limits. Her abdominal ultrasound was also normal. While waiting for further results, she was started on lamivudine (100 mg daily). However, total HBV core antibody test was negative. Owing to the infrequency of this serological pattern, an in vitro polymerase chain reaction (PCR) assay was performed and HBV was not detected. Overall, we interpreted these results as a false-positive screening. Methylprednisolone pulse therapy was subsequently given (1 g daily for three doses) without hepatic repercussion, neither clinically nor biochemically. Conclusions: Isolated HBsAg positivity may result from multiple causes, one of which is crossreactivity. To the best of our knowledge, this is the first report of a false-positive reading using CMIA technique in an active lupus patient. It is reasonable to stress that lupus patients with a positive screening for HBV should undergo a confirmatory assay (such as genomic detection), since this diagnosis may have important therapeutic implications. 2016 Egyptian Society of Rheumatic Diseases. Publishing services provided by Elsevier. B.V. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/)